Concept of Ar-Rahn in Islamic finance : another alternatives - A. Rahim, M. Zamir Azfar; A. Halim, M. Hafizuddin; Zulkifli, M. Mokhzani; Kayadibi, Saim (IIUM Press, 2011)
In today's world more people rely on getting money by mortgaging their properties. It is done because of many reasons such as maintaining daily life or funding the expensive tertiary studies. In today's conventional mortgage has prove that by pledging their properties it could be risky and may end up leaves them at worst homeless. It is because the interest in today's conventional mortgage seems to be a burden to some people.Base on this situation, many people especially Muslim are becoming aw'are and change their choice from conventional mortgage to more Islamic way which is Ar-Ralm. It is mention in Al-quran is that as a Muslim he/she should take Ar-Rahn. Plus the cons in conventional mortgage is that it is heavily rely on riba which is vel)' clearly stated it is Haram for a muslim to be involved with them